Brucellosis in Dallas, Texas: a Case Series. (4th October 2017) - Quadri, Syeda; Cutrell, James; Nijhawan, Ank E
Abstract: Background: While the epidemiology of Brucellosis is well described in systematic reviews and retrospective analyses in endemic countries, there is a paucity of similar data in the United States (US). With a recent outbreak of Brucellosis reported in Dallas County in 2016, we sought to characterize cases of Brucellosis at two Dallas teaching hospitals over the past 10 years. Methods: A retrospective chart review of electronic medical records at Parkland Health and Hospital System and Clements University Hospital was completed for all patients over 18 who were diagnosed with Brucellosis, as defined by ICD9/10 codes, problem lists, and/or positive microbiologic or serologic data, between 1/1/2007 - 2/6/2017. Demographic, epidemiologic, and clinical characteristics were collected. Results: Out of 104 charts reviewed, 16 cases of Brucellosis (14 definite, 2 probable) were identified. Fifty-six percent were male, the mean age was 45, and 94% were of Hispanic ethnicity. Recent travel was reported in 6/16 cases (5 to Mexico, 1 to India) and exposure to unpasteurized cheeses was reported in 13/16 cases. The majority of cases were seen in the summer months, and a sharp increase in incidence was noted in 2016 (Figure 1). Common symptoms included fever (16/16), chills (8/16), diarrhea (4/16), headache (4/16), malaise (4/16), and body aches (4/16). Laboratory abnormalities included leukopenia, thrombocytopenia, and elevated liver function tests. Other complications included epididymitis and/or orchitis (2/16), hepatomegaly (5/16), splenomegaly (4/16), and other splenic abnormalities (2/16). Brucella discitis/osteomyelitis with spinal epidural abscess (1/16), possible neurobrucellosis (1/16) and recurrent disease (2/16) were also identified. The most common treatment regimen used was doxycycline/rifampin +/- gentamicin. Conclusion: This case series represents one of the largest contemporary Brucella experiences described in the US. While not endemic in the US, the diagnosis of Brucellosis requires a high index of suspicion and should be considered in patients presenting with a febrile illness and a compatible travel history or exposure history, particularly to unpasteurized dairy products. Disclosures: All authors: No reported disclosures.